Design, synthesis and neuroprotective activity of compound derived from Gastrodia elata Blume and borneol - Zhi, Lijuan; Li, Huan; Shi, Baimei; Yu, Tao; Jia, Xiaoni; Zhang, Hui (Frontiers in Pharmacology, 2024)
Introduction Traditional Chinese medicine Gastrodia elata Blume (GEB) possesses properties that soothe the liver and dispel wind. Its constituents exhibit numerous pharmacological properties, including neuroprotective effects, analgesic properties for headache relief, memory enhancement, and others. Borneol enhances drug absorption by traversing the blood-brain barrier, thereby improving its bioavailability and therapeutic efficacy. The research aimed to design innovative drug molecules and contribute to the beneficial exploration of compound Chinese medicine modernization. Methods This study employed the strategy of “compound Chinese medicine molecular chemistry” to integrate and fuse the effective substances of compound Chinese medicines. An excitotoxic injury model was established by exposing PC12 cells to glutamate. Cell viability was quantitatively evaluated utilizing a colorimetric assay with the CCK-8 reagent kit. Genecards, Disgenet, and OMIM databases were used to identify potential disease-related targets. Molecular docking methods were performed to predict the binding interactions between compounds and core targets. Results We designed and synthesized compounds TB-1 to TB-16. Following the evaluation of their safety, TB-1, TB-2, TB-12, and TB-16 were selected for further investigation of their neuroprotective properties. The compound designed in this study exhibits a dose-dependent protective effect on glutamate-damaged PC12 cells. Further network pharmacology and molecular docking analyses indicate that TB-2 possesses a potential therapeutic effect against cerebral ischemia, and its possible targets were SRC, MAPK1 and KDR. Discussion The results indicated that TB-2 displayed a significant neuroprotective effect against Glu-induced injury in PC12 cells, suggesting potential therapeutic implications for cerebral ischemia.